Salivary Protein Profiles among HER2/neu-Receptor-Positive and -Negative Breast Cancer Patients: Support for Using Salivary Protein Profiles for Modeling Breast Cancer Progression - Streckfus, Charles F. (Hindawi Publishing Corporation, 2012)
Purpose. The objective of this study was to compare the salivary protein profiles from individuals diagnosed with breast cancer that were either HER2/neu receptor positive or negative. Methods. Two pooled saliva specimens underwent proteomic analysis. One pooled specimen was from women diagnosed with stage IIa HER2/neu-receptor-positive breast cancer patients (n = 10) and the other was from women diagnosed with stage IIa HER2/neu-receptor-negative cancer patients (n = 10). The pooled samples were trypsinized and the peptides labeled with iTRAQ reagent. Specimens were analyzed using an LC-MS/MS mass spectrometer. Results. The results yielded approximately 71 differentially expressed proteins in the saliva specimens. There were 34 upregulated proteins and 37 downregulated proteins.